Existence and stability of some fractional differential equations in the framework of Ulam–Hyers–Rassias - Bouzid, Azzedine Kaddour; Bougoutaia, Amar (Laghouat : Université Amar Telidji - Département de mathématiques, 2025)
The objective of this thesis is to study some qualitative properties of solutions for various classes of nonlinear fractional , we begin by convert the problem umber considered into an equivalent integral equation and using the fixed point theorem . We finish by given example for each problem consider.